Farmers’ awareness and perceptions on Newcastle disease in chicken: Evidence from high and low rainfall regions of Kenya - Billy Okemer Ipara; David Jakinda Otieno; Rose Adhiambo Nyikal; Nabwile Stellah Makokha (Cogent Food & Agriculture, 2024)
Newcastle disease (ND) poses a major challenge to Kenyan farmers who raise local chicken in a free-range system. The lack of consistent poultry rearing practices makes it unclear how farmers manage the disease. Insufficient awareness and negative perceptions contribute to the problem, leading to poor management and increased disease outbreaks. The extent of Kenyan farmers’ awareness and perceptions of ND also remains poorly documented. This study examined ND awareness, perceptions, and factors influencing awareness using a binary logit model on data from 332 farmers in high rainfall (Kakamega) and low rainfall (Machakos) regions in Kenya. Limited access to support services (34% extension, 25% training and 25% credit) was observed. The ND was perceived as a significant chicken disease, causing high mortality and losses during outbreaks. Awareness of ND was higher in high-rainfall areas. The household type, access to extension services and credit, training, and group membership significantly influenced ND awareness. Strengthening group membership is recommended for improved access to relevant information. Kakamega and Machakos county governments should invest more in targeted extension services, potentially collaborating with private providers and development partners. Financial institutions should also tailor their products to fit chicken farmers’ needs.